Long‐term outcomes of metabolic surgery in overweight and obese patients with type 2 diabetes in Asia. Issue 3 (23rd December 2020) - Huang, Yu‐Min; Lin, Yen‐Kuang; Lee, Wei‐Jei; Hur, Kyoung Yul; Kasama, Kazunori; Cheng, Anton Kui Sing; Lee, Ming‐Hsien; Wong, Simon Kin‐Hung; Soong, Tien‐Chou; Lee, Kuo‐Ting; Lomanto, Davide; Lakdawala, Muffazal; et al.
Abstract: Aim: To assess the outcomes of metabolic surgery in overweight and obese patients in Asia with type 2 diabetes (T2D). Materials and Methods: The treatment outcomes of 1999 patients from the Asian Diabetes Surgery Summit database were analysed. The changes in treatment effects across time were assessed with respect to the surgical procedures performed by using generalized estimating equations. Results: The most commonly performed procedure was the single‐anastomosis gastric bypass (32.6%). Weight (from 106.2 ± 25.1 to 77.9 ± 18.8 kg), body mass index (BMI; from 38.7 ± 7.9 to 28.5 ± 5.9 kg/m 2 ), blood sugar (from 9.3 ± 4.1 to 5.7 ± 1.8 mmol/L) and HbA1c (from 8.4% ± 1.8% to 6.0% ± 1.1%) significantly improved from baseline to 1 year ( P < .001) and remained stable at 5 years (weight, 86.3 ± 23.3 kg; BMI, 31.7 ± 7.9 kg/m 2 ; blood sugar, 5.8 ± 1.8 mmol/L, and HbA1c, 6.4% ± 1.2%; all P < .001 vs. baseline). Blood pressure and most lipid disorders also improved significantly. Of the treatment procedures, single‐anastomosis gastric bypass had the most satisfactory outcomes with statistical significance for most disorders, whereas adjustable gastric banding displayed the least satisfactory outcomes. Conclusions: Metabolic surgery remarkably improved body weight, T2D and other metabolic disorders in Asian patients. However, the efficacy of individual procedures varied substantially.